Nutraceutical eicosapentaenoic acid in treatment-resistant depression: The psychoneuroimmunity and clinical implications - Jane Pei-Chen Chang; Ayesha Zafar Iqbal; Quang Le Do; Muhammad Yaseen; Suet-Kei Wu; Ikbal Andrian Malau; Halliru Zailani; Kuan-Pin Su (Pharmacological Research)
Treatment Resistant Depression is characterized by inadequate response to at least two adequate trials of antidepressants, highlighting the need for alternative or adjunctive strategies. Emerging evidence suggests omega-3 polyunsaturated fatty acids, particularly eicosapentaenoic acid, may offer therapeutic benefits in the management of Treatment Resistant Depression. A total of twelve studies, including randomized controlled trials and open label studies, with a combined sample size of 498 participants have reported encouraging outcomes with eicosapentaenoic acid -predominant omega-3 polyunsaturated fatty acids in Treatment Resistant depression. The proposed mechanisms underlying these effects include the anti-inflammatory actions, neuroprotection, and modulation of neurotransmitter systems. This review focuses on key biological systems potentially influenced by eicosapentaenoic acid in the context of Treatment Resistant Depression, including damaged-associated molecular patterns, endocannabinoid system, gut-brain axis, and specialized pro-resolving lipid mediators. Additionally, we examine the therapeutic potential of eicosapentaenoic acid in Treatment Resistant Depression with coexisting medical conditions, such as obesity and pain.